Perencanaan Bisnis Katering Bayi Dan Anak Maestro di Kota Semarang - Tri Artika Sari (Soegijapranata Catholic University, 2019)
Abstract: This study aims to find out business planning on Catering Babies and Children Maestro in Semarang City in terms of marketing, operational, human and financial resources. The location of this research is in Semarang. While the object of research that will be lifted in this research is about analysis of business planning of Catering Maestro: Baby and Child Catering in Semarang City. This business plan covers aspects of marketing, human resources, operations, and finances of a business. The type of data in this study are primary and secondary data. In this study, the data collection tool uses: Library Studies and Interviews. Problem solving to be done by the researcher use two approach that is descriptive analysis qualitative. Based on the results of the analysis and discussion can be drawn conclusion as follows: